Peningkatan Hasil Belajar Siswa Menggunakan Model Discovery Learning Pada Pembelajaran Tematik Terpadu Kelas IV Sekolah Dasar - Sari, Putri Anggelia; Yunisrul, Yunisrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research is to describe the planning, implementation and improvement learning outcomes of students using a discovery learning model in integrated thematic learning in grade IV Elementary School. In this study applying the type of PTK research uses qualitative and quantitative approaches. Where this research was conducted on class IV B SDN 34 Simpang Haru Kota Padang totaling 27 people consisting of 11 male students and 16 female students. The results of the study in the first cycle of learning outcomes reached a percentage of completeness of 55,56%  (enough category) with an average value of 73,1 (good category) increased in the second cycle percentage of completeness 96,3% (very good category) with an average achievement of 86,7 (very good category).